Masterworks of 20th-Century Music : the Modern Repertory of the Symphony Orchestra. - Lee, Douglas (Taylor and Francis, 2013)
""Masterworks of 20th-Century Music"" introduces more than one hundred of the greatest compositions by world-renowned composer that have entered the standard orchestral repertory. The author surveyed dozens of major American orchestras to focus on those works that an average audience member is most likely to hear. Concertgoers who are intimated by the modern repertoire finally have a single resource that will help them understand and enjoy it. Like an educated guide, he walks the listener through the piece, explaining how all the elements come together to form a unified whole. This.